Current-Sensorless Energy-Shaping Output Voltage-Tracking Control for dc/dc Boost Converters With Damping Adaptation Mechanism - Kim, Seok Kyoon; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2022)
This article exhibits an output voltage-derivative observer-based output voltage-tracking technique for dc/dc boost converters without current feedback, taking the model-plant mismatches (caused by parameter and load variations) and model nonlinearity into consideration. In contrast to extant passivity-based approaches, the proposed solution includes observers to estimate the output voltage derivative and does not require exact model information, which offers a few features: converter parameter information-free output voltage-derivative observers including the modified disturbance observation algorithm for improving the high-frequency disturbance rejection capability as a replacement of the estimation error integral actions, and the observer-based output voltage and its derivative error stabilizer with a damping adaptation mechanism assigning the desired energy function to the closed-loop system. Experimental verification is provided to demonstrate the practical advantages of the proposed solution using a 3-kW bidirectional converter.
Keywords: Adaptation mechanism; Convergence; Damping adaptation; Dc - dc boost converters; Load modeling; Observer; Output voltages; Time-varying systems; Voltage tracking; Voltage-derivative observer; Damping adaptation; dc/dc boost converter; energy dissipation; voltage tracking; voltage-derivative observers